2016
DOI: 10.1080/19490976.2016.1218584
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic perturbation of the preterm infant gut microbiome and resistome

Abstract: The gut microbiota plays important roles in nutrient absorption, immune system development, and pathogen colonization resistance. Perturbations early in life may be detrimental to host health in the short and the long-term. Antibiotics are among the many factors that influence the development of the microbiota. Because antibiotics are heavily administered during the first critical years of gut microbiota development, it is important to understand the effects of these interventions. Infants, particularly those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 51 publications
2
72
0
Order By: Relevance
“…The acquisition of the first microbial colonizers may be altered by multiple maternal and infant factors, which may result in differences in oral microbiota development. These factors could include mode of delivery, breastfeeding, pregnancy outcomes, parental contact, antibiotics, host factors and living environment, all of which have been recognised to affect infant’s intestinal microbial habitat1926272829. It is however not clear if, and to what extent, these factors contribute to shaping the oral microbiome.…”
mentioning
confidence: 99%
“…The acquisition of the first microbial colonizers may be altered by multiple maternal and infant factors, which may result in differences in oral microbiota development. These factors could include mode of delivery, breastfeeding, pregnancy outcomes, parental contact, antibiotics, host factors and living environment, all of which have been recognised to affect infant’s intestinal microbial habitat1926272829. It is however not clear if, and to what extent, these factors contribute to shaping the oral microbiome.…”
mentioning
confidence: 99%
“…Furthermore, the presence of AMR elements in the infant gut does not seem to be influenced by selective pressures from foodborne or administered antibiotics [50]. However, in preterm infants, there is evidence of selective negative pressure on meconium bacterial richness depending on antibiotic administered, with ticarcillin-clavulanate, and cefotaxime showing the greatest effects [51, 52]. Thus, as antibiotics are prescribed routinely in preterm and low birthweight infants for preventing necrotizing enterocolitis, spread of AMR in the preterm infant gut should be a factor of concern in the context of long-term intestinal and immune health, and must be addressed in longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%
“…Infants, particularly those born prematurely, represent an interesting population because they received early and often extensive antibiotic therapy in the first months after birth [32]. Gibson et al recently demonstrated that children who had been exposed to antibiotic therapy had a dramatical reduction in the diversity of their microbial population.…”
Section: Antibiotic Exposures Impair the Diversity And Stability Of Gmentioning
confidence: 99%
“…More interestingly, the researchers also observed that some children harboured antibiotic resistance genes as early as 2 months of age, before any antibiotic treatments. In recent report, researchers from Washington University School of Medicine (WUSM) demonstrated that gut microbiota in healthy American children also carried a large number of antibiotic resistance genes, likely to make harmful effects [32].…”
Section: Gut Microbiota Carried Antibiotic Resistance Genementioning
confidence: 99%
See 1 more Smart Citation